PREFERENSI PASANGAN INFERTIL DALAM MEMILIH KLINIK INFERTILITAS - Natasha Susanto Utomo (Jurnal Manajemen Pelayanan Kesehatan (The Indonesian Journal of Health Service Management), 2024)
Background: There has been increasing need for access to infertility care in Indonesia, leading several hospitals to establish infertility centers. RS Permata Hati Metro opened it’s infertility clinic to improve access and quality of infertility services. As competition grows with other hospitals also providing infertility sevices, it is crucial for RS Permata Hati Metro to understand the preferences of infertile couple to tailor their marketing startegies effectively.Objectives: To identify the preferences of infertile couples at the RS Permata Hati Metro Infertility Clinic regaring desired infertility services.Methods: This observational analytic study used a cross-sectional design and conjoint analysis. The sampel consisted of infertile couples who visited the clinic from April 2022 to April 2023.Results: Success rate were identified as the most critical attribute in the decision-making process of infertile couples, at 46.64%, followed by the completeness of examination and treatment facilities (17.83%), the experience of the attending doctor (13.75%), service cost (12.78%), and the recommender (9%). Positive utility values indicated that recommendations from friends or family (0.014), the experience of specialist doctor who are fertility consultants (0.361), comprehensive examination facilities (0.361), higher success rates (1.011), and lower service costs (0.240). There was no significant difference in the order of attribute importance and utility values between wives and husbands.Conclusions: A combination of attributes such as recommendations from friend or family, specialist doctors who are fertility consultants, comprehensive examination facilities, higher success rates, and lower service costs provide the most positive influence on infertile couples in choosing an infertility clinic.